Passed, regulated, or applied? The different stages of emigrant enfranchisement in Latin America and the Caribbean. Issue 3 (3rd April 2019) - Palop-García, Pau; Pedroza, Luicy
ABSTRACT: When are emigrants really enfranchised? Lengthy lags exist between some reforms that de jure introduced external voting and their application. In the blooming literature on emigrant enfranchisement, these lags remain unexplained. We argue that this hampers our understanding of enfranchisement processes as having different legal and political stages. With data on Latin American and Caribbean states since 1965 until the present, we investigate why some states in this region have delayed the regulation and application of external franchise while others have implemented it right after enactment. We propose hypotheses to understand these reforms as episodes marked by different contexts, engineered by different agent coalitions and embedded into larger processes of political change. In particular, we suggest that enfranchisement processes are composed of three stages: enactment, regulation, and first application. Our findings suggest that the process of adoption of external voting is shaped by the legal mechanism of enactment and the stability of political coalitions.